Investigating the effects of previous injury on subsequent training loads, physical fitness, and injuries in youth female basketball players - Huang, Yuanqi; Wang, Shaonan; Li, Changfei; Wang, Yukun; Bai, Zhanshuang; Lv, Binghao; Gui, Yuheng; Wei, Zhongjian (Frontiers in Physiology, 2025)
BackgroundPrevious studies have shown that athletes accustomed to higher chronic workloads are less susceptible to injury than those exposed to lower chronic workloads. However, few studies have evaluated whether previous injury influences them. Therefore, this study investigated the impact of previous injuries on subsequent training loads, physical fitness, and injury rates in female youth basketball players.MethodsTraining load, physical fitness, and injuries of 18 young female basketball players (age 16.8 ± 1.4 years) were monitored. Previous injury status was clustered using the K-means clustering algorithm to separate players into high-risk and low-risk groups. Linear mixed models were used to analyze the effects of previous injury status on subsequent training load and physical fitness. Meanwhile, the differences between the players’ injury groups were analyzed.ResultsPrevious injury status can significantly impact a player’s subsequent training loads, including acute loads, chronic loads, skill-based training loads, training monotony, and training strain (all p < 0.05). The two groups had no significant differences in physical fitness (all p > 0.05). Furthermore, the incidence of non-contact injuries was significantly higher in the high-risk group than low-risk group, which would result in more training time lost (all p < 0.05).ConclusionThis study identified the impact of previous injury status on subsequent training load, physical fitness, and injuries in youth female basketball players. These findings provide valuable insight for coaches to optimize training loads according to previous injury status, aiming to minimize the likelihood of subsequent injuries.